2002
DOI: 10.1103/physrevb.66.224406
|View full text |Cite
|
Sign up to set email alerts
|

Spin-12J1J2model on the body-centered cubic lattice

Abstract: Using exact diagonalization (ED) and linear spin wave theory (LSWT) we study the influence of frustration and quantum fluctuations on the magnetic ordering in the ground state of the spin-1 2 J1-J2 Heisenberg antiferromagnet (J1-J2 model) on the body-centered cubic (bcc) lattice. Contrary to the J1-J2 model on the square lattice, we find for the bcc lattice that frustration and quantum fluctuations do not lead to a quantum disordered phase for strong frustration. The results of both approaches (ED, LSWT) sugge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 27 publications
7
63
0
Order By: Relevance
“…17 On the other hand, recently it has been found that the 3d J 1 -J 2 model on the body-centered cubic lattice does not have an intermediate quantum paramagnetic phase. 18,19 Moreover, in experimental realizations of the J 1 -J 2 model the magnetic couplings are expected to be not strictly 2d, but a finite interlayer coupling J ⊥ is present. For example, recently Rosner et al…”
Section: -489mentioning
confidence: 99%
“…17 On the other hand, recently it has been found that the 3d J 1 -J 2 model on the body-centered cubic lattice does not have an intermediate quantum paramagnetic phase. 18,19 Moreover, in experimental realizations of the J 1 -J 2 model the magnetic couplings are expected to be not strictly 2d, but a finite interlayer coupling J ⊥ is present. For example, recently Rosner et al…”
Section: -489mentioning
confidence: 99%
“…A lot of activities in this area were focused on frustrated spin-half Heisenberg antiferromagnets like the J 1 -J 2 antiferromagnet on the square lattice (see, e. g. [18][19][20][21][22][23][24][25][26][27][28] and references therein) and on three-dimensional cubic lattices [29][30][31][32][33], the Heisenberg antiferromagnet (HAFM) on the star lattice [12,11,34] and last but not least the HAFM on the kagomé lattice (see the reviews [11,[35][36][37] and references therein). Due to the extreme frustration, the HAFM on the kagomé and on the star lattices shows an infinite non-trivial degeneracy of the classical ground state.…”
Section: Introductionmentioning
confidence: 99%
“…As in other cases, there are various possibilities for the subgroups of translations which define the PBC. These subgroups are generated by three vectors called "edge vectors" [26]. For our purposes these finite pyrochlore lattices are interesting, since they provide the first examples of lattices admitting a-LM states with codimension higher than one.…”
Section: Higher Codimension Type Pyrochlore Latticementioning
confidence: 99%